The Development of Oyster Farming in Italy: An Innovation Opportunity for Mollusks Farming Diversification - Elena Tamburini; Edoardo Turolla (2023)
Pacific oyster (Crassostrea gigas Thunberg, 1793) is the most farmed and consumed bivalve worldwide, with over 6,000,000 tons and a global market value of about 58 billion USD, in 2020 [1]. As aquaculture in general, its production is expected to rapidly grow in the next years, and to play a key role in food security [2]. In fact, except for some developed countries where oysters are considered a luxury food, globally they are widespread in the human diet, as fresh or processed food (i.e., Far-East coastal countries). Although native to the Pacific area, this species is now considered cosmopolitan as it was accidentally or voluntarily introduced into many temperate geographical areas, including the Italian coasts and the Po Delta, where it has been present since the second half of the 1960s. Its large diffusion is due to the wide tolerance and rapid growth performance. In fact, it is an estuarine species that can survive both on stable bottoms, fixed to solid substrates, as reefs or rocks, and on muddy or sandy-muddy bottoms, from the mid-tidal area to 40 m depth, in a range 0.5%-3.5% salinity and -2°C to 35°C temperature [3]. In Italy, oysters are definitely an appreciated product, but today almost all of them are imported, especially from France. National production is, in fact, still almost completely negligible, less than 300 tons/year, compared with an annual consumption of around 10,000 tons.